Cancer patients' needs for support in expressing instrumental concerns and emotions. (7th August 2019) - Linn, Annemiek J.; van der Goot, Margot J.; Brandes, Kim; van Weert, Julia C. M.; Smit, Edith G.
Abstract: Introduction: The aim of our study was to provide an overview of intervention guidelines on how to address patients' practical needs for support in expressing instrumental concerns and emotions regarding medical, psychosocial and practical topics. Methods: Six focus groups of cancer patients and survivors ( N =  39) were organised. An interview guide was created that consisted of three topics: (a) concerns, (b) needs for support, and (c) a Concern Prompt List. Using the framework method, the transcripts were coded and analysed in Atlas T.I. Results: Patients prefer to receive practical and emotional support, help with preparation, prompts/cues, instructions on how to perform the behaviour (i.e., express their concerns or emotions), feedback, a different structure for the consultation and tailoring. Most of these techniques should preferably be delivered via interpersonal communication. Needs sometimes differ for instrumental concerns and emotions. Only some needs for support were exclusively related to instrumental concerns or emotions. The typical needs for support were not solely linked to the medical, psychosocial and practical topics. Conclusion: Different needs to express instrumental concerns and emotions throughout the disease trajectory are categorised. These needs provide input for developing interventions to support concern expression.